Cars, Creditors, and the Code: The Diverse Interpretations of Section 9-310 - Arthur G. Murphey Jr. (Washington University Law Quarterly, 1970)
This is a brief survey of statutory interpretation. It is a study of what courts have done in the past, on the theory that this may offer suggestions to courts faced with a similar problem in the future. It is limited to one particular priority conflict—that between a lender with a perfected security interest in an automobile and a repairman with a lien for work he has done on that automobile.
Keywords: Commercial law; Motor vehicles; Statutes